Empoderamiento familiar y su incidencia en la inclusión laboral de los usuarios del Centro Diurno Mies Loja - Quezada Armijos, Mónica Andrea (2024)
This study analyzes the incidence of familiar empowerment in labor inclusion of people with disabilities that attend the day center of Integral Attention for people with disabilities MIES Loja. The labor inclusion still presents several limitations and barriers for people with disabilities, these impediments are not only present in the lack of job opportunities, but also in discrimination and stigmatization by employers. The objective of this research work is to analyze the impact of family empowerment on the labor inclusion of the users of the Integral Development Day Center for people with disabilities. The methodology began by defining the research design characterized as non-experimental, since no variable was manipulated, the research is basic since it seeks to support and expand theoretical knowledge, focused on improving the understanding of the problem without trying to solve or present any intervention proposal, which is why a mixed approach was used, applying a quantitative instrument in which surveys were conducted to the families of users and a qualitative technique through semi- structured interviews with facilitators and social worker. Finally, the results show that family empowerment has a relevant impact on the labor inclusion of users, since empowered families tend to actively participate in the labor inclusion process, thus facilitating access to employment opportunities. Thus, the strengthening of family competencies and institutional support are fundamental to improve the labor inclusion of people with disabilities.